The role of intermediaries in connecting community-dwelling adults to local physical activity and exercise: a scoping review - Barrett, Emer; Connolly, Deirdre; O'Grady, Megan; Mockler, David; Broderick, Julie; Kennedy, Megan (My University, 2023)
Introduction/Purpose Physical inactivity has been declared a global pandemic by the World Health Organization. Methods to connect inactive individuals from healthcare settings to physical activity include brief interventions and exercise referral schemes. These have a number of limitations, such as inconclusive evidence of long-term effectiveness and a lack of training and implementation. An intermediary is a professional who can facilitate and support connections to non-medical community services, such as physical activity. As this is an emerging method to tackle physical inactivity, the processes used by intermediaries has not been clearly documented. Therefore the purpose of this review was to identify and describe the available international evidence regarding referral to an intermediary, and the processes and outcomes of connecting individuals to physical activity services. Methods This scoping review was carried out according to guidelines from the Joanna Briggs Institute. An extensive electronic database and grey literature search was conducted from inception to June 2022. Full-text peer reviewed and non-peer reviewed studies that reported on the process of an intermediary, after receiving a referral for a community-dwelling adult, in connecting them to physical activity services were considered for inclusion. Two independent reviewers screened articles, with a third author available as arbitrator. Data were charted using an a priori form, and descriptive statistics were used to summarise the included studies. A logic model was created to map the processes to outcomes, and a patterns, advances, gaps, evidence and research recommendations table was created to identify evidence advances and gaps. Findings The search identified 10257 citations, and 35 individual research reports were included, the majority of which were from the UK and USA. Fourteen reports used quantitative designs, seven used qualitative designs, and the remainder had mixed/other methods. Over 10,000 individuals were referred to an intermediary. They tended to be older, female, and with poorer health. Other demographic information such as marital status and education levels were poorly reported. The intermediaries had diverse backgrounds in healthcare, physical activity and community care and received high levels of training. Diverse, heterogeneous processes of referral, assessment, follow-up and discharge by intermediaries were identified and described. Individuals were commonly connected to fitness or walking groups in the community. Positive outcomes were reported at short-term follow-up in relation to attendance and participation, steps per day, physical activity levels, energy expenditure, physical fitness and sedentary behaviour. Discussion/Research Implications An intermediary is an emergent inter-sectoral approach between healthcare, community & voluntary and physical activity sectors to tackle physical inactivity. Physical activity outcomes tended to be positive. However, quality of evidence was not rated and a scoping review cannot determine causation or correlation. Some aspects of the processes of an intermediary remain poorly described, such as the assessment, the onward connection to local physical activity, detailed components of follow-up, and discharge. More research is needed to explore these preliminary positive physical activity outcomes. However, further studies of the processes of intermediaries are needed to explore implementation factors, mechanisms of impact and contextual factors in order to inform the design of future trials.
NUIG Health Promotion Annual Conference
PUBLISHED
Galway
Keywords: PHYSICAL ACTIVITY; physical activity promotion; Chronic Health Condition; Health